Reliable determination of the few‐layer graphene oxide thickness using Raman spectroscopy. (26th November 2015) - Kostiuk, Dmytro; Bodik, Michal; Siffalovic, Peter; Jergel, Matej; Halahovets, Yuriy; Hodas, Martin; Pelletta, Marco; Pelach, Michal; Hulman, Martin; Spitalsky, Zdenko; Omastova, Maria; Majkova, Eva
Abstract : We report on a reference‐free Raman spectroscopy method for a precise thickness determination of the multilayered graphene oxide flakes. The method is based on the normalization of the total integral intensity of D and G Raman bands to the integral intensity of the second‐order optical phonon peak of the silicon substrate in the Raman spectrum. The normalization provides discrete ratio values corresponding to the number of graphene oxide layers in the respective flakes with the intensity linearly increasing with the number of layers. This provides a fast and robust determination of the thickness of graphene oxide flakes in terms of the layer number up to high values. A comparison with conventional spectrally resolved reflectivity mapping shows similar sensitivity, while selectivity to particular functional chemical groups is a bonus of the Raman‐based method. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The conventional Raman spectroscopy methods used for graphene are not applicable for graphene oxide due to the reduced interlayer vibrations. We employed normalization of the total D and G band integral intensity to the integral intensity of the second‐order optical phonon peak of silicon